Implementation of an Independent Learning Curriculum to Improve Non-Academic Achievement of Students in SD Plus Latansa Demak - Rachim, Rynaldi Setya; Naela Khusna Faela Shufa; Tito Pangesti Adji; Dinar Ayu Mirunggan Sari (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the implementation of Merdeka Curriculum on improving students' non-academic achievement at SD Plus Latansa Demak. The Merdeka Curriculum is the result of adaptation to learning needs in the digital era, by giving students the freedom to develop their potential outside of academics. In this study, the author uses a qualitative approach to explore how the implementation of the Merdeka Curriculum can improve students' non-academic achievement through organized and interest- and talent-based activities. The results of this study indicate that the implementation of Merdeka Curriculum has great potential in optimizing students' non-academic achievements, with support from more flexible curriculum management, technology-based learning, and intensive assistance to teachers.With the implementation of the Merdeka Curriculum, students can be freer to explore their interests and talents outside the classroom, which can help them develop their previously untapped potential. Through organized and interest- and talent-based activities, students can feel more motivated and excited about learning, so that their non-academic achievements can also improve significantly.